New trends in the training process of athletes specializing in motorcycle crosscountry racing with sidecar motorcycles - Sova Maria; Volodymyr Shishka (Kharkiv State Academy of Physical Culture, 2019)
The purpose of the study is to justify the methods of special physical training of athletes in motocross on motorcycles with a side trailer, taking into account their individual characteristics. Research objectives: To develop a methodology for training athletes specializing in motocross motorcycles with a sidecar, taking into account the specific interaction of crew members. Material and research methods: a pedagogical experiment was organized in order to compare the technical and tactical indicators of the competitive activity of world leaders and leading Ukrainian crews in cross-country motorcycle riding with wheelchairs, and justification, on this basis, of methodological recommendations for preparing our athletes for participation in international competitions the highest level. Results apparent difference in the speed of the distance between world and Ukrainian leaders indicates a significantly higher level of special, functional and technical preparedness of the former, which at higher speeds overcome obstacles at a distance, demonstrating a high level of universality of their preparedness. It has been revealed that the special physical training of our athletes is a reliable reserve for increasing their sports performance.Conclusions. Application of the methodology for constructing a qualitative structure of competitive motor activity of athletes in cross-country on motorcycles with heelchairs made it possible to stablish that the leading motor quality is special agility. The second most important in ensuring a high sports result in cross-country on motorcycles with wheelchairs is the general and special endurance of crew members.